Otimização da técnica eletroquímica de reativação potenciodinâmica de ciclo duplo (DL-EPR) para avaliação da resistência à corrosão localizada de cladding de aço inoxidável duplex UNS S39209 em aço carbono - Canal, André (2017)
Duplex stainless steels (AIDs) belong to a group ofmaterials of high mechanical and corrosion propertiesperformance.These achievements have been investigatedby several works on theapplication ofthe cladding weld with these materialsdue to the greater pitting resistance equivalente number (PREN) than conventional austenitic stainless steels and their lower costcompared withsuperalloys.During the deposition processthe cooling rate can influence the microstructural balance (δ and ) and the incidence of deleterious phases, which can decrease the performance of the deposited material.In this work the optimization of the parameters of theDouble Loop Electrochemical PotentiokineticReactivation(DL-EPR) for evaluatingquantitativelytheeffectof the dilution on the localizedcorrosion resistance ofcladding of UNS S39209 deposited by GTAWwelding with cold wire onASTM A36 steel.The microstructural characterization was performed by optical microscopy before and after the corrosion tests.Theefectsof thescanning rate and concentration of thedepassivator HCl in the solutionon the relationship betweenactivation and reactivation currents, which quantifies the corrosion resistance,were investigated.The results demonstrated that thesolution of33% H2SO4+ 0.5% HCl and scan rate of 1.5 mV/s can characterize the interactions between precipitation and chromium depletion of the deposited material.A decrease of the localized corrosion resistance was observed for higher austenite contents. The presence of secondary austenite and chromium nitrideswas detected in thespecimenof lower dilution. In the intermediate dilution specimenonly chromium nitrides were observed. However, these specimensshowna lower degree of sensitization than the specimenwith the highest dilution